Low concentration fertigation solution allows greater macronutrient use efficiency in coffee seedlings - Rosa, Kelly Martins; Paiva, Paulo Eduardo Branco; Coelho, Victor Peçanha de Miranda; Carvalho, Mychelle; de Assis, Henrico Luis Bizão [UNESP] (Coffee Science, 2021)
Coffee seedling production in cone-shaped containers and substrate results in lower sanitary risk and costs. With the use of small containers and substrates with low fertilizer levels, fertigation is necessary for seedling development. An experiment was carried out with three macronutrient concentrations (electrical conductivities of 1.0, 2.0 and 3.0 dS m-1) and a non-fertilized control using Coffea arabica cv. Topázio seedlings in 50 cm3 cone-shaped containers and composted pine bark-based substrate. The following fertilizers (expressed in g m-3 of water) were used in the nutrient solution with EC of 1.0 dS m-1: Ca(NO3)2 (400), KNO3 (250), MgSO4 (175), (NH4)PO4 (50) and ConMicros Standard® (25). In the solutions with 2.0 and 3.0 dS m-1, macronutrient concentration was doubled and tripled, while micronutrients remained the same. At four months we assessed EC and pH of the solution drained, shoot dry mass, shoot nutrient concentration and accumulation and macronutrient use efficiency. Fertigation with 1.0 and 2.0 dS m-1 produced seedlings with greater mass (+10%) than fertigation with 3.0 dS m-1, while higher macronutrient supplies increased shoot N, P, K, Mg and S concentration. Fertigation with 2.0 dS m-1 caused greater shoot N, P, K and Ca accumulation and this conductivity also resulted in higher accumulation of B, Fe, Mn and Zn without increasing the micronutrient supply. The response to the increase in Ca in the nutrient solution is evident in the accumulation of this nutrient in the plant but not its concentration, possibly due to the dilution effect. Micronutrient accumulation in this species is also more adequate for determining nutritional status than the concentration in the plant. The least concentrated macronutrient solution increases nutrient use efficiency in C. arabica seedlings as well as being economically and environmentally more sustainable.
Keywords: Coffea arabica; Electrical conductivity; Nutrition; PH; Substrate